Eksperimental Variasi Kecepatan Putar Screw Feeding Dengan Kecepatan Putar PIsau Pengupas Terhadap Kualitas Hasil Pengupasan Pada Mesin Pengupas Kulit Pinang - Hakim, Hasanul; Yohanes, Yohanes; Kurniawan, Iwan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The processing of areca nut at the present time is still done manually and requires a long working time. To facilitate the skinner process and optimize the results that required a technology of machine which paring the areca nut skin. The Skinner machine of areca nut at this point still has deficiency. For resolving the problems that exist on the areca nut skinner machine which has type of screw then troubleshoot by varying the rotational speed of the screw feeding toward skinner tool of areca nut. After tested with variations of the rotational speed of the screw feeding to ward skinner tool of areca nut, then obtained the optimal results as much as 6 pieces and other 4 pieces of areca nut already broken on screw feeding speed at 37 rpm and 800 rpm on a skinner tool. The time that required to perform the paring process on this rotational speed is 21.7 seconds. The optimal skinner Results of areca nut increases to 9 pieces after made the casing modification which the efficiency of time is 73.5%Key Words :Kernel of areca, optimalization, rotational of correlation, rotational speed,time